PRODUCTION OF MONOCLONAL ANTIBODY AGAINST DOMOIC ACID (DA) BY MURINE HYBRIDOMA USING CONDITIONED CELL CULTURE MEDIUM IN VITRO - A. F. Saeed1; S. Awan (Journal of Animal and Plant Sciences, 2017)
Domoic acid is a highly potent marine toxin which is produced by Pseudo-nitzschia. It causes amnesic shellfish poisoning in humans after consumption of contaminated shellfish. In the present study, hybridoma technology has been used to develop a murine hybridoma cells producing monoclonal antibody by the conditioning of cell culture media with different carbohydrates in vitro. Carbohydrates are important organic enhancements in cell culture media that considerably increase hybridoma cell growth and antibody production.Indirect enzyme-linked immunosorbent assay was established to determine the antibody titers of cell culture supernatants. A hybridoma C4H5 cell line was developed by the fusion of Sp2/0 myeloma cells with spleen cells that were harvested from Balb/c mice immunized with complete DA antigen.The influence of carbohydrates on cell growth and higher protein production of C4H5 cells has been investigated. Galactose, fructose and maltose significantly increased protein production by the factor of 1.7, 2.0 and 2.2, respectively.The study extends understanding of augmented use of superior carbohydrate in cell culture media to improve growth of hybridoma cells and subsequently higher yields of antibody.
Keywords: Domoic acid; Amnesic shellfish poisoning; Cell culture; Hybridoma; Monoclonal antibody; Fetal bovine medium; Carbohydrates